Electroforesis en gel de campo pulsado (PFGE) para la diferenciación molecular de Listeria monocytogenes (2013)
The reporting of L. monocytogenes in food in Colombia is not a mandatory; however, foods considered high-risk are monitored, and the organism is only reported clinically as Gram-positive when it causes meningitis. L. monocytogenes is a foodborne, intracellular, pathogen which causes listeriosis, a disease lethal to humans and animals. Outbreaks of this disease worldwide can bring about human and economic losses. Only a few studies in Colombia have been able to identify and molecularly serotype isolates allowing only the theoretical distribution of serotypes by lineage. This review explains the characteristics of the pathogen, its importance in public health and in the food industry, and provides an overview of PFGE-CHEF; identifying the standard work protocol and the appropriate restriction enzymes to cut DNA. We found that the enzyme combination, XbaI-AscI, followed by ApaI offers the best results to differentiate isolates, by grouping them by lineages, and displaying intra-serotype variations. Additionally, we found that in several Latin American countries the results are analyzed using PulseNet; this ensures the comparison of PFGE patterns in equivalent conditions.